The Nurses' Role in Management Complaint - Wahyuningsih, Aries; Firmanda, Giovanni Iga; Pratiwi, Wahyu Nur; Margaretta, Sheylla Septina (Babali Publisher, 2024)
Background: As primary caregivers, nurses ensure patient safety and quality health services by effectively managing patient complaints. Proper handling of these complaints is crucial for providing effective treatment. Develop management and understanding of handling patient complaints efficiently by providing a systematic framework and identifying effective communication techniques to deal with patient complaints effectively. Methods: ProQuest, Ebsco, Science Direct, and Elsevier were the literature sources examined between 2013 and 2023. Results: Nursing managers should enhance nurses' communication skills to improve patient care and complaint management. Studies indicate that targeted training in communication significantly boosts nurses' effectiveness and patient satisfaction.Conclusion: Implementing training programs, regular assessments, and ongoing support will improve patient outcomes and more effective complaint handling.